1996
DOI: 10.1038/ki.1996.301
|View full text |Cite
|
Sign up to set email alerts
|

Renal nitric oxide synthases in transgenic sickle cell mice

Abstract: The alpha H beta S [beta MDD] mouse is a useful model for studying renal functional abnormalities in sickle cell disease. We previously reported that these mice develop a urine concentrating defect when chronically exposed to a low oxygen environment. In the present study, we measured glomerular filtration rate (GFR), urinary excretion of NO2 s+ NO3, the stable products of nitric oxide (NO), and the abundance of endothelial constitutive nitric oxide synthase (NOS III) and inducible nitric oxide synthase (NOS I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
59
1
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 38 publications
6
59
1
1
Order By: Relevance
“…The occurrence of xanthine oxidasederived, O 2 . -dependent inhibition of ⅐ NO-mediated vascular relaxation in SCD vessels (53) and the elevated expression of NOS2 (54,55) in the kidney and liver of SCD mice and human ( Figs. 1 and 2) also reinforces the concept that elevated rates of production of the oxidizing and nitrating species ONOO Ϫ occurs in SCD.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of xanthine oxidasederived, O 2 . -dependent inhibition of ⅐ NO-mediated vascular relaxation in SCD vessels (53) and the elevated expression of NOS2 (54,55) in the kidney and liver of SCD mice and human ( Figs. 1 and 2) also reinforces the concept that elevated rates of production of the oxidizing and nitrating species ONOO Ϫ occurs in SCD.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that iNOS inhibition significantly limits tissue ischemiareperfusion injury in the liver and kidneys [10][11]; however, inhibition of iNOS attenuated ischemiareperfusion injury in the rat heart [12], but not in the rat lung [13]. Increased iNOS expression was reported in the kidneys of transgenic mice [9], but Nath et al [14] reported the lack of iNOS upregulation in intrarenal vasculature and increased iNOS expression in the glomeruli and distal tubules of sickle mice. Previous attempts to demonstrate increased iNOS expression in SCD-affected tissues have yielded inconclusive results [52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…SCD is also strongly associated with oxidative stress, increased expression of endothelial cell adhesion molecules, and blood adhesion. Increased iNOS expression and NO production have been observed in the kidneys and the liver in SCD patients [8], in mice [2,3,8,9], and in pigs [4]. During the clinically asymptomatic state, NO bioavailability is reduced in SCD patients due to scavenging of NO by cell-free hemoglobin released from hemolyzed sickle erythrocytes [50] and increased arginase activity [51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations